Use of an audience response system during a continuing education action about oral lesion diagnosis. Issue 12 (25th July 2022) - Herpich, Tiago Luís; Kovalski, Luan Nathiel Santana; Roxo‐Gonçalves, Michelle; Romanini, Juliana; Carrard, Vinicius Coelho
Abstract: Objectives: The present cross‐sectional study aimed to evaluate the perceptions of continuing education action (CEA) participants on the use of an audience response system (ARS). Secondarily, the study assessed the association between the diagnostic abilities of participants and their self‐confidence in managing oral lesions Methods: Oral medicine specialists, dentists, hygienists, and students ( n = 193) who attended the 'Maio Vermelho Project', a CEA held in a Southern Brazilian State, answered a diagnostic ability test using the ARS Socrative software during a case discussion section. The test comprised 16 simulated clinical cases based on photos of oral lesions. The questions required classification of the lesion's nature, diagnostic hypothesis, and decision making (manage the case or refer it to a specialist) for each case. A second questionnaire composed of 12 questions was also applied to evaluate satisfaction and perception of the use of ARS Socrative Results: Hygienists displayed lower scores in the diagnostic abilities test, whereas the other groups' performances were quite similar. Dentists and dental students who scored higher on the diagnostic abilities test showed higher self‐confidence in the management of benign lesions. All participants stated that the use of technology can improve their learning experience and should be incorporated into the classroom. Moreover, the participants' perception was highly favorable to the use of Socrative in educational activities Conclusion: Our findings showed good acceptance of the ARS tool in a CEA environment and suggest an association between performance on the questionnaire and self‐confidence in oral lesion management.